APLIKASI MIKROKONTROLER AT89S52 UNTUK KOMPAS DIGITAL - Bustanul Arifin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2007)
The aim of this research is to design and testing for digital compass with CMPS03 sensor product by Devantech, Ltd, AT89S52 microcontroller, 128x64 pixel LCD Graphic Display. The experiment design to hardware and software. Hardware systems consist several of part, identification system and component choosing. Where as, the design of LCD display and microcontroller programming are software design with SDCC Compiler C language.  The result of research showed value 2.30 for accuration and 0.10 for resolution CMPS03 digital compass.